2015
DOI: 10.1007/s12149-015-1021-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone scan index change over time on automated calculation in bone scintigraphy

Abstract: BONENAVI reading of BSIs and hot spot numbers was highly affected by acquisition time. In serial or follow-up examinations (in particular, for monitoring therapeutic efficacy), acquisition time should be fixed for each patient. Cautious interpretation should be made on segments with high physiological uptake. BONENAVI reading was prone to misinterpretation of artifacts. Visual assessment is necessary to rule out this possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Most single-institution studies (n = 9/25, 36%) originated from the United States; moreover, most of the multi-institutional studies included an American center (n = 6/9, 67%) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Five studies originated from Germany [ 23 , 24 , 25 , 26 , 27 ], four from Sweden [ 28 , 29 , 30 , 31 ], and six from Japan [ 32 , 33 , 34 , 35 , 36 , 37 ]. Information about patient number, acquisition technique, type of employed isotope (when applicable) and method of computational analysis were obtainable from all studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most single-institution studies (n = 9/25, 36%) originated from the United States; moreover, most of the multi-institutional studies included an American center (n = 6/9, 67%) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Five studies originated from Germany [ 23 , 24 , 25 , 26 , 27 ], four from Sweden [ 28 , 29 , 30 , 31 ], and six from Japan [ 32 , 33 , 34 , 35 , 36 , 37 ]. Information about patient number, acquisition technique, type of employed isotope (when applicable) and method of computational analysis were obtainable from all studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the work from Shintawati and co-workers, BSI was evaluated on bone scan acquired at different time points after injection [ 34 ]. The index increased significantly from 2 h p.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BSI values obtained at 2, 4, and 6 h after injection with 99m Tcmethylene diphosphonate were significantly different from each other. Therefore, the study recommended that time interval should be near constant in a clinical follow-up study (8). The present study is part of the continual effort to identify the procedural factors in image acquisition that significantly influence the BSI quantification of bone and therefore need standardization in prospective multiinstitutional clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of variability in these preanalytical factors on the quantitative assessment of bone scan via automated BSI is largely unknown. A recent Japanese study found that the BSI assessment of bone scan was dependent on the time between the tracer administration and scanning and recommended that the time interval should be near constant in a clinical follow-up study (8). Qualification of BSI as an imaging biomarker hinges on the identification and subsequent standardization of such procedural factors that significantly affect the performance of the automated BSI assessment.…”
mentioning
confidence: 99%